1991
DOI: 10.1152/ajpcell.1991.260.4.c731
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transport, Ca2(+)-ATPase, and lipid order in rabbit ocular lens membranes

Abstract: Calcium transport was monitored by measuring ATP-dependent 45Ca uptake into membrane vesicles prepared from rabbit lens cortex. Calcium-stimulated adenosinetriphosphatase (Ca2(+)-ATPase) activity was also measured in the same membrane preparation. Both uptake and Ca2(+)-ATPase activity were inhibited by vanadate. Calcium activation of the uptake process was similar to that of the Ca2(+)-ATPase. Calcium uptake was prevented by calcium ionophore A23187, suggesting that the calcium transported into the vesicles r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…We have shown previously that the Ca 2ϩ -ATPase activity in the lens was correlated to lipid order. 80,81 SR Ca 2ϩ -ATPase, reconstituted into ordered (about 40% trans) lens lipids, were five times less active than when reconstituted with native SR lipids. 81 It has been established that in synthetic lipid systems, the mobility of a probe in the lipid bilayer (except in the case of lipids completely in the gel or liquid crystalline phase) does not correlate with Ca 2ϩ -ATPase activity.…”
mentioning
confidence: 91%
“…We have shown previously that the Ca 2ϩ -ATPase activity in the lens was correlated to lipid order. 80,81 SR Ca 2ϩ -ATPase, reconstituted into ordered (about 40% trans) lens lipids, were five times less active than when reconstituted with native SR lipids. 81 It has been established that in synthetic lipid systems, the mobility of a probe in the lipid bilayer (except in the case of lipids completely in the gel or liquid crystalline phase) does not correlate with Ca 2ϩ -ATPase activity.…”
mentioning
confidence: 91%
“…Based on the findings that lipids with highly structurally ordered hydrocarbon chains, completely in the trans conformation, inhibit Ca# + -ATPase activity, and that, in general, the conformation of biomolecules influence their interactions, it is reasonable to speculate that the relatively high hydrocarbon order of bovine lens lipids (Borchman, Cenedella and Lamba, 1996c) contribute to the inhibition of the pump. It has been shown that the hydrocarbon trans rotomer content directly correlated with the Ca# + -ATPase activity and calcium translocation in rabbit lens cortical microsomes (Delamere et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium homeostasis is essential to the maintenance of lens clarity (Clark, Bagg and Benedek, 1980 ;Hightower and Reddy, 1982) and the Ca# + -ATPase pump is essential for the removal of cytosolic calcium either across the plasma membrane (Delamere et al, 1991 ;Borchman, Delamere and Paterson, 1988 ;Galvin and Louis, 1988) or into internal organelles such as the endoplasmic reticulum (Duncan et al, 1993). The lens contains comparable amounts of two isoforms of Ca# + -ATPase, the SERCA and PM types (Zeng, Borchman and Paterson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…More ordered membranes arc less permeable to oxygen and cations [ 13]. The other phospholipids are more 'fluid' [6] and are possibly necessary to provide a fluid matrix that supports pump [7] and enzyme activity. DHS undoubtedly provides structur al order to the hydrocarbon chain region and upholds the integrity of the membrane under oxidative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this study is on hydrocarbon chain structure. We have previously used spectroscopic techniques such as infrared [6][7][8][9] and FTRaman [10] and dispersive Raman [11] techniques to charac terize lens lipid hydrocarbon chain structure in human and rabbit lenses.…”
Section: Introductionmentioning
confidence: 99%